Emerging Adjuvants for Cancer Immunotherapy - Hu, Hong-Guo; Li, Yan-Mei (Frontiers in Chemistry, 2020)
Cancer is a life-threatening disease, and immunotherapies have been developed as a novel, potent treatment for cancer. Adjuvants, used alone or in combination with other agents, play crucial roles in immune activation. This is necessary for cancer immunotherapy, particularly in the construction of therapeutic cancer vaccines. Adjuvants activate antigen-presenting cells and promote the presentation of antigen epitopes on major histocompatibility complex molecules, further enhancing adaptive immune responses, including cytotoxic T lymphocytes, to elicit cancer-cell death. However, the applications of adjuvants are limited by their poor efficacy or insufficient safety. In recent studies, researchers attempted to develop safe, efficacious adjuvants for cancer immunotherapy, and many compounds (including inorganic compounds, organic molecules, polymers, and colloids) have been identified and optimized as agonists of various pathways. In this review, we focus on the discovery and structural design of emerging adjuvants and discuss how these findings benefit healthcare.